2018
DOI: 10.1093/ibd/izy004
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Patients With Inflammatory Bowel Disease: Results of 2 Prospective Cohort Studies

Abstract: Sex differences in patients with IBD include age of onset, disease location, and EIM prevalence. No large differences in therapeutic management of IBD were observed between men and women with IBD. 10.1093/ibd/izy004_video1izy004_Video_15786481854001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 28 publications
7
69
1
3
Order By: Relevance
“…They were more often diagnosed with ileal disease and they underwent more often small bowel and ileocaecal resection. 32 In our cohort, rates of previous resection between men and women were similar.…”
Section: Discussionsupporting
confidence: 49%
“…They were more often diagnosed with ileal disease and they underwent more often small bowel and ileocaecal resection. 32 In our cohort, rates of previous resection between men and women were similar.…”
Section: Discussionsupporting
confidence: 49%
“…Data regarding sex differences in the incidence, disease severity, response to medications, and mortality of IBD patients are limited and inconclusive (45,46). However, the presence of sex differences in IBD in patients is indicated by several lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of 51.7% is higher than that seen in male counterparts as well as in the ageand sex-matched general population (26.6%) [24]. Accordingly, a Dutch study revealed that more women than men are current smokers in the IBD population [17]. Long time ago, the following dogma was established and has been supported since: smoking is protective in UC, while it has deleterious effects in CD patients.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In Europe and the United States, CD prevalence appears to be higher in females than in males [8][9][10][11][12][13], while in Asia the opposite has been observed [14][15][16]. Early-onset CD (< 16 years) has been reported to be more frequent in males than females (20 vs. 12%) [17]. A recent large investigation revealed an even more complex relation between sex and IBD epidemiology [18].…”
Section: Epidemiologymentioning
confidence: 99%